2013
DOI: 10.1155/2013/906820
|View full text |Cite
|
Sign up to set email alerts
|

Dye-Sensitized Solar Cell Based on Polyaniline/Multiwalled Carbon Nanotubes Counter Electrode

Abstract: This work presented the successful fabrication of dye-sensitized solar cell using polyaniline base (EB), multiwalled carbon nanotubes (MWCNTs), organic dye (rhodamine B or riboflavin), zinc oxide (ZnO), and indium tin oxide (ITO). The electrical properties of the resultant devices were investigated by measuring the current density voltage (J-V), capacitance voltage (C-V), and impedance measurements under both dark and illuminated conditions. The photovoltaic cell characteristics, that is, open circuit voltage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…However, this is still an emerging topic of research; therefore the studies dedicated to it seem scarce, regardless of the potential shown. An investigation on electrospun PLA/PANI nanofibers for rigid and flexible DSCs [198] and another on PANI/MWCNT counter electrodes [199] are among the few studies conducted.…”
Section: Applications Of Electrospun Pani Nanofibersmentioning
confidence: 99%
“…However, this is still an emerging topic of research; therefore the studies dedicated to it seem scarce, regardless of the potential shown. An investigation on electrospun PLA/PANI nanofibers for rigid and flexible DSCs [198] and another on PANI/MWCNT counter electrodes [199] are among the few studies conducted.…”
Section: Applications Of Electrospun Pani Nanofibersmentioning
confidence: 99%
“…18 Polyaniline (PANI) possesses a large amount of amine and imine functional groups, which can interact with metal ions. [19][20][21][22] PANI has been used for adsorbing different heavy metal ions due to its porous structure, regeneration, nontoxicity, insolubility in water, high stability and low cost. 19,20 The incorporation of NPs into PANI does not only solve the agglomeration problem but can also improve the properties of the PANI matrix.…”
Section: Introductionmentioning
confidence: 99%
“…In different three protonation concentrations of PANI are zero-protonated, halfprotonated, and fully protonated thin films, current-voltage measurements shows that conversion efficiency of 1.3%. Ebrahim et al [2] reported the dye-sensitized solar cell based on PANi/ multiwalled carbon nanotubes composite as a counter electrode. The electrical properties of fabricated devices analyzed using by measuring current density, voltage, capacitance voltage, and impedance under both dark and illuminated conditions.…”
Section: Introductionmentioning
confidence: 99%